Global trends in diabetes complications: a review of current evidence - Harding, Jessica L.; Pavkov, Meda E.; Magliano, Dianna J.; Shaw, Jonathan E.; Gregg, Edward W. (Diabetologia, 2019)
In recent decades, large increases in diabetes prevalence have been demonstrated in virtually all regions of the world. The increase in the number of people with diabetes or with a longer duration of diabetes is likely to alter the disease profile in many populations around the globe, particularly due to a higher incidence of diabetes-specific complications, such as kidney failure and peripheral arterial disease. The epidemiology of other conditions frequently associated with diabetes, including infections and cardiovascular disease, may also change, with direct effects on quality of life, demands on health services and economic costs. The current understanding of the international burden of and variation in diabetes-related complications is poor. The available data suggest that rates of myocardial infarction, stroke and amputation are decreasing among people with diabetes, in parallel with declining mortality. However, these data predominantly come from studies in only a few high-income countries. Trends in other complications of diabetes, such as end-stage renal disease, retinopathy and cancer, are less well explored. In this review, we synthesise data from population-based studies on trends in diabetes complications, with the objectives of: (1) characterising recent and long-term trends in diabetes-related complications; (2) describing regional variation in the excess risk of complications, where possible; and (3) identifying and prioritising gaps for future surveillance and study.